A Conformationally Flexible Dinuclear PtII Complex with Differential Behavior of its Two States toward Quadruplex DNA. Issue 34 (12th July 2013) - von Grebe, Philipp; Suntharalingam, Kogularamanan; Vilar, Ramon; Sanz Miguel, Pablo J.; Herres‐Pawlis, Sonja; Lippert, Bernhard
Abstract The reaction of tetrakis(pyridine‐2‐yl)pyrazine (tppz) with 2 equiv of (2, 2′‐bpy)PtII in water yields two isomeric dinuclear cations, [{Pt(2, 2′‐bpy)}2(tppz)]4+, in which Pt coordination exclusively takes place through the two pairs of pyridine‐2‐yl nitrogen atoms. The two conformational isomers differ in their overall shape, with the formation of "Z" and "U" shapes, which are formed at 40 °C (Z isomer, 1) and under reflux conditions (U isomer, 2), respectively. X‐ray crystal‐structure analyses of the Z isomer, [{Pt(2, 2′‐bpy)}2(tppz)](PF6)4⋅3 CHCl3⋅4 H2O (1 a), and of the U isomer, [{Pt(2, 2′‐bpy)}2](PF6)4⋅2 CH3CN⋅1.5 H2O (2 a), were carried out. Co‐crystallization of compound 2 with PtCl2(2, 2′‐bpy) yielded [{Pt(2, 2′‐bpy)}2(tppz)](BF4)4⋅[PtCl2(2, 2′‐bpy)]⋅4.5 H2O (3), in which the PtCl2(2, 2′‐bpy) entity was sandwiched between the two 2, 2′‐bpy faces of the U‐shaped cation (2). Quantum chemical calculations revealed that the U isomer was more stable than the Z isomer, both in the gas phase and in an aqueous environment. These two isomers display different affinities toward duplex DNA and human telomeric quadruplex DNA (Htelo), as concluded from CD spectroscopy and FID assays. Thus, the U isomer binds significantly more strongly to quadruplex DNA (DC50=0.38 μM) than the Z isomer (DC50=8.50 μM).